Development of system-based digital decision support (“Pocket Ark”) for post-flood enhanced response coordination and worker safety: an Intervention Mapping approach - Perkison, William Brett; Shegog, Ross; Lai, Dejian; Upadhyay, Saswati; Yalavarthy, Geethika; Guerrero-Luera, Rosalia; Mathews, Patenne D.; Rios, Janelle; Mehta, Ritesh; McLaughlin, Jeffery; Nabeel, Ismail (Frontiers in Environmental Health, 2024)
Background The health and safety of workers who work in areas severely damaged by natural weather events (reconstruction workers) is becoming an increasingly important health problem as these disasters increase in intensity and frequency. An evidence-based, innovative e-learning tool, Pocket Ark, has been developed to meet this need. Methods Intervention Mapping, an iterative public health programming methodology, was used to create strategies designed to support the development and implementation of the Pocket Ark application for the health and safety of reconstruction workers before, after, and during natural disasters. Discussion The development of an evidence-based application, Pocket Ark, uses the concept of the Intervention Mapping planning framework. It can be an effective bridge of pre-deployment education, deployment health, and safety support for the reconstruction work in the immediate post-disaster environment.